Â¬Â¬Rancang Bangun Sistem Informasi Persetujuan Dokumen Menggunakan Openssl Dan Digital Signature Berbasis Web - Alcianno G. Gani; Qori Hanifah (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
The development of technology in the world helps all fields in providing efficient and effective solutions. One example in everyday life in the work environment is the process of document approval flow starting from document submission, examination, and recording of all document approval activities. The submission starts from a sender who will file the document. The submitted documents will be examined by the examiner who is referred to as the verifier. Verifier required as many as 2 people. The verifier will check that the submitted document is appropriate or not. The process is problematic for the authenticity of an agreement because through communication media measured by authenticity cannot be done. This research aims to ensure that the approval given is genuine or not then uses the process of openssl and digital signature. The subject in this study was how to create a document approval information system application by adding to the opensl and digital signature process in verifying the authenticity of the verifier's approval. The process uses the laravel php framework programming language. The application development step starts with collecting the required data from interviewing and viewing existing flow processes, designing, coding and testing the system. The result of this study is an output that produces an application that can ensure the authenticity of document approval using openssl and digital signature where there is a notification to the email of each verifier.